2006
DOI: 10.1016/j.jcrs.2005.12.135
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral cefazolin as prophylaxis against endophthalmitis in cataract surgery

Abstract: Intracameral bolus injection of cefazolin (1 mg in 0.1 mL solution) in cataract surgery demonstrated prophylactic efficacy in diminishing the rate of postoperative endophthalmitis without toxic effects on the cornea or retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 19 publications
3
79
0
Order By: Relevance
“…51 Similar results have been obtained in studies using intracameral cefazolin (1mg or 2.25mg per 0.1ml) at the end of cataract surgery. 52,53 An eleven year study in more than 50000 Asian patients by Tan et al reported a decrease in the rate of endophthalmitis from 0.064% to 0.010% after the addition of 1mg in 0.1ml intracameral cefazolin. 54 It has been shown that using intracameral cefuroxime prevents 1 case of endophthalmitis for every 182 patients treated, thus providing a very favourable outcome in terms of the healthcare budget.…”
Section: Intracameral Antibioticsmentioning
confidence: 99%
“…51 Similar results have been obtained in studies using intracameral cefazolin (1mg or 2.25mg per 0.1ml) at the end of cataract surgery. 52,53 An eleven year study in more than 50000 Asian patients by Tan et al reported a decrease in the rate of endophthalmitis from 0.064% to 0.010% after the addition of 1mg in 0.1ml intracameral cefazolin. 54 It has been shown that using intracameral cefuroxime prevents 1 case of endophthalmitis for every 182 patients treated, thus providing a very favourable outcome in terms of the healthcare budget.…”
Section: Intracameral Antibioticsmentioning
confidence: 99%
“…The addition of gentamicin and vancomycin to the irrigating fluid during phacoemulsification results in a highly significant reduction in the microbial contamination of AC aspirates. 64 Also, many studies have proved the efficacy of intracameral antibiotics in the prevention of postoperative endophthalmitis. Intracameral bolus injection of cefazolin (1 mg in 0.1 ml solution) and also intracameral cefuroxime 1 mg at the end of cataract surgery have been shown to reduce the rate of postoperative endophthalmitis without toxic effects on the cornea or retina.…”
Section: Triazole Agentsmentioning
confidence: 99%
“…Furthermore, the concentration of these antibiotics used in irrigating solutions and the duration that they are in contact with bacteria responsible for endophthalmitis are not enough to be effective, based on their bactericidal or bacteriostatic characteristics (Peck et al, 2010). Other authors described the use of intracameral cefotaxime (Kramann et al, 2001), cefazolin (Garat et al, 2005) (Romero et al, 2006), and cefuroxime (Díez et al, 2009), but no toxicity has been reported. Nevertheless, there is always a possibility that these antibiotics could result in TASS due to an error in drug concentration or pH.…”
Section: Antibioticsmentioning
confidence: 99%
“…Intracameral cefazoline been reported to be used in several papers mainly from Spain. Its choice as a prophylactic agent for postoperative endophthalmitis is based on the bacteria cultures and antibiograms from their own cases and data published (Garat et al, 2005) (Romero et al, 2006). These authors believe that the first-generation cephalosporin cefazoline 1 mg in 0.1 ml of saline injected in anterior chamber has a broader spectrum of activity against gram-positive bacteria than the second-generation cefuroxime.…”
Section: Antibiotics Employed In the Operating Roommentioning
confidence: 99%